English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Need assistance with the following problem: if f(x) = 1 + x^2 and g(x) = sqrt (x-1) what is g o f and (f o g)(2)

2007-03-19 16:38:23 · 3 answers · asked by brain9storm 1 in Science & Mathematics Mathematics

3 answers

g o f (x) = sqrt((1 + x^2) - 1) gof(2) = sqrt((1 + 2^2) -1) = sqrt(4) = 2
f o g(x) = 1 + (sqrt(x-1))^2 fog(2) = 1 + (sqrt(2-1))^2 = 1 + 1^2 = 2

2007-03-19 16:47:26 · answer #1 · answered by dylan k 3 · 0 0

I don't really understand what is g o f and (f o g)(2).
But I assume g o f is [gf(x)] and (f o g)(2) is [fg(2)].

f(x) = 1 + x^2 and g(x) = (x -1)²

[gf(x)]
= g(1 + x²)
= [(1 + x²) - 1]²
= 1² + 2x² + x^4 - 1²
= 2x² + x^4 (final answer)

If you want to find [gf(2)]
= 2x² + x^4
= 2(2)² + 2^4
= 8 + 16
= 24 (final answer)

f(x) = 1 + x² and g(x) = (x -1)²

[fg(x)]
= f(x -1)²
= 1 + [(x -1)²]²
= 1 + (x² - 2x + 1²)²
= 1 + x^4 - 2x² + 1^4
= x^4 - 2x² + 1

[fg(2)]
= x^4 - 2x² + 1
= 2^4 - 2(2)² + 1
= 16 - 8 + 1
= 9 (final answer)

2007-03-19 17:21:45 · answer #2 · answered by dchosen1_007 2 · 0 0

First for f(g(x)), this suggests that as quickly as you come back throughout an "x" interior the f(x) equation, you plug interior the g(x) value. So the problem might appear as if 3(x^2) so the respond for f(g(x)) could be 3x^2. For g(f(x)) you do an identical ingredient; once you come back throughout an "x" in that equation, plug interior the cost this is f(x). So the equation might appear as if (3x)^2. So the respond for g(f(x)) is 9x^2.

2016-12-18 18:23:33 · answer #3 · answered by ? 3 · 0 0

fedest.com, questions and answers